2011
DOI: 10.1093/brain/awq386
|View full text |Cite
|
Sign up to set email alerts
|

Fumaric acid esters exert neuroprotective effects in neuroinflammation via activation of the Nrf2 antioxidant pathway

Abstract: Inflammation and oxidative stress are thought to promote tissue damage in multiple sclerosis. Thus, novel therapeutics enhancing cellular resistance to free radicals could prove useful for multiple sclerosis treatment. BG00012 is an oral formulation of dimethylfumarate. In a phase II multiple sclerosis trial, BG00012 demonstrated beneficial effects on relapse rate and magnetic resonance imaging markers indicative of inflammation as well as axonal destruction. First we have studied effects of dimethylfumarate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
917
2
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 983 publications
(962 citation statements)
references
References 52 publications
25
917
2
18
Order By: Relevance
“…In the cuprizone model, mice receiving DMF displayed reduced demyelination,20 a result that has been suggested to be due to reduced microglia activation. These results were similar to EAE results, which demonstrated reduced demyelination associated with reduced immune cell infiltration, astrocyte activation, and increased cytoprotection 2. In MS patients, DMF treatment significantly increased brain magnetization transfer ratio, suggesting increases in myelin density 21.…”
Section: Introductionsupporting
confidence: 87%
See 4 more Smart Citations
“…In the cuprizone model, mice receiving DMF displayed reduced demyelination,20 a result that has been suggested to be due to reduced microglia activation. These results were similar to EAE results, which demonstrated reduced demyelination associated with reduced immune cell infiltration, astrocyte activation, and increased cytoprotection 2. In MS patients, DMF treatment significantly increased brain magnetization transfer ratio, suggesting increases in myelin density 21.…”
Section: Introductionsupporting
confidence: 87%
“…To date, direct comparisons of fumarates on human and murine glial cells have not been performed. In addition, the biological role(s) of the active metabolite of DMF treatment has been controversial, with evidence supporting that both MMF2, 29 and DMF9, 16 modulate anti‐inflammatory and antioxidant effects. Although the debate against DMF has been widely attributed to previous reports citing the inability to measure biologically significant concentrations in the brain and periphery, a recent report has shown that DMF is indeed present in the CNS following oral administration 16…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations